Economic analysis of a customer-installed energy storage system for both self-saving operation and demand response program participation in South Korea - Kang, Byung O.; Lee, Munsu; Kim, Youngil; Jung, Jaesung (Renewable and Sustainable Energy Reviews, 2018)
In recent years Energy Storage System (ESS) has become increasingly important, not only for reducing peak customer demand, but also for enhancing grid stability and reliability. In this manner, this paper performs an economic analysis when a customer-installed ESS is used to both reduce their peak demand and participate for grid stability and reliability in the South Korean Demand Response (DR) program. First, current government policies for accelerating the utilization of ESS and compensation rules of the DR program in South Korea are investigated. Then, an optimal operational strategy for ESS is developed to maximize profits from DR program participation while maintaining the ESS self-saving operation (peak shaving and arbitrage). Actual industry demand profiles are used to verify the effectiveness of the proposed operational strategy for ESS. Furthermore, sensitivity analysis is performed by varying the DR program conditions to facilitate ESS participation. Therefore, these suggestions provide an effective guideline to encourage more ESS to participate in DR program in the future.
Keywords: Arbitrage; Demand response; Economic demand; Economic demand response; Energy storage system; Peak-shaving; Reliability demand; Reliability demand response; Storage systems; Arbitrage; Demand Response (DR); Economic DR; Energy Storage System (ESS); Peak shaving; Reliability DR